DINAMIKA PERKAWINAN USIA DINI DALAM UNDANG-UNDANG PERKAWINAN - Wibowo, Irham; Pobela, Mohammad Ramsliyanto (Jurnal GeoCivic, 2024)
Early marriage is a social phenomenon that often occurs in many countries, including Indonesia. The phenomenon of early marriage is like an iceberg, but in reality, if we trace the history of early marriage, there are certainly many causes. In fact, there are extramarital marriages carried out by the younger generation and this often occurs due to economic problems, level of education, cultural practices and loss of religious values. There is a negative stigma against women who marry at an early age. Marriage is a strong bond to become a sakinah, mawaddah and rahmah family, which is structured according to legal principles, both Islamic law and state law. Marriage law regulates the limits on those who may marry, material requirements, and age limit provisions contained in Law Number 1 of 1974 concerning Marriage as amended by Law Number 16 of 2019. This article will discuss official marriage in Islamic law.